Communicating in groups : applications and skills - Adams, Katherine L.; Galanes, Gloria J. (McGraw-Hill, 2012)
Offers a step-by-step introduction to the theory and practice of small group communication and teaches students to develop and apply critical thinking skills in group problem-solving situations. Suitable for students interested in the dynamics of small group communication, this book synthesizes small group theory and research